رسول اللہ ﷺ کا بالوں میں خضاب لگانے سے متعلق روایات کا تحقیقی جائزہ: A research review of traditions related to applying hair dye to Rasulullah ﷺ - Muhammad Abdul ul Naseer Alvi, (MEI, 2023)
There is a difference of opinion between the scholars on whether the Messenger of Allah (P.B.U.H.) himself dyed his hair. However Abu Bakar and Umar ibn al-Khattab (Allah be pleased with them) did dye the hair of their head and beard, thus it will be classed as recommended (mandub), if not Sunnah. He (P.B.U.H.) also stated: “The best dye to change your old age is “Hinna” (a red plant dye) and Katm (type of grass)”. The Holy Prophet (P.B.U.H.) said: “There will be people who will come later (in my Ummah) and apply black dye. They will not even smell the fragrance of paradise” However other scholars including the great Hanafi jurist and student of Imam Abu Hanifa, Imam Abu Yusuf (Allah have mercy on him) permitted the use of black dye for adornment, especially the wife, to adorn herself for her husband. It has also been narrated from some of the companions such as: Sayyiduna Uthman, Sayyiduna Hasan, Sayyiduna Husain & others (Allah be pleased with them all) that they used black colour dye. “The final word regarding the using of black dye is that, it will not be considered unlawful (haram), although disliked (makruh). The prohibition in the Hadith will be understood to be confined in the situation when one uses it to deceive others”. It should also be remembered here that the above discussion is when the dye is pure black. However, if it is not pure, rather it is dark and black-inclined; it would be permissible to apply it. In conclusion, it is recommended to dye the hair (for men and women) with other than pure black colour. To use pure black dye in order to deceive others is unlawful (haram)